Unravelling drug resistance in leishmaniasis: genomic adaptations and emerging therapies - Bhusal, Chandra Kanta; Sinha, Shweta; Kaur, Davinder; Sehgal, Rakesh (Frontiers in Molecular Biosciences, 2025)
Leishmaniasis remains a significant global health challenge, with over a billion people at risk of infection and limited effective treatment options due to escalating drug resistance. This review explores the underlying mechanisms of drug resistance in Leishmania species, focusing on genomic plasticity as a driving factor for survival and adaptation. Key mechanisms, including genetic mutations, gene amplification, chromosomal rearrangements, and efflux transporters, contribute to the parasite’s ability to evade existing therapies. Advances in genomic and proteomic studies have provided deeper insights into these resistance pathways, enabling the development of novel therapeutic strategies. Additionally, this review highlights current therapeutic approaches, including combination therapies and potential new drug candidates, that address multidrug resistance and explore the vulnerabilities of Leishmania. Understanding these mechanisms and their clinical implications is essential for developing targeted interventions that improve treatment outcomes and combat resistance in leishmaniasis.